Linguistic fieldwork a student guide - Sakel, Jeanette 1973-; Everett, Daniel Leonard (Cambridge, [England] Cambridge University Press, 2012)
"A handy beginner's guide, this textbook introduces the various stages of linguistic fieldwork, from the preparation of the work to the presentation of the results. Drawing on over forty years of fieldwork experience between them, in over two dozen languages, the authors pack the book with examples and anecdotes from their experiences and include practical exercises for students to test what they have learned. Independent of any particular perspective, the methods can be applied to a wide range of fieldwork settings, for projects with very different theoretical backgrounds and without the need to travel too far. The book covers 'traditional fieldwork' such as language description and documentation, as well as less typical methods, including language contact and quantitative studies with experiments or questionnaires"--Provided by publisher.
Machine generated contents note: 1. Introduction: what is linguistic fieldwork? -- 2. Fieldwork projects: two examples -- 3. The languages -- 4. The people -- 5. Fieldwork preparation -- 6. Fieldwork methods -- 7. The outcomes.
Keywords: Linguistics -- Fieldwork; Languages, Modern -- Study and teaching -- Handbooks, manuals, etc